2007
DOI: 10.1007/s10620-007-0039-3
|View full text |Cite
|
Sign up to set email alerts
|

Wedged Hepatic Venous Pressure Does Not Reflect Portal Pressure in Patients with Cirrhosis and Hepatic Veno–Venous Communications

Abstract: Some cirrhotic patients have hepatic veno-venous communications (HVVC) and large porto-systemic collaterals. However, the relationship between wedged hepatic vein pressure (WHVP) and portal vein pressure (PVP) in such patients is not clear. The aim of this study was to determine the relationships between simultaneously measured WHVP and PVP, and occluded hepatic and splenic portal venography in 100 cirrhotic patients (40 alcoholic and 60 hepatitis C virus (HCV)-related cirrhosis). PVP and WHVP were closely rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…One is the presence of communications between intrahepatic vessels, such as VVC, which is common in noncirrhotic patients. Previous studies have shown the incidence of VVC to be 55% in noncirrhotic patients, 100% in IPH, and 13-35% in patients with cirrhosis [19,20,32]. A second factor is the difference in the venous pressures in the different hepatic vein branches, with one report indicating that a single venous measurement may underestimate the risk of bleeding from esophageal varices in 13% of cirrhotic patients [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One is the presence of communications between intrahepatic vessels, such as VVC, which is common in noncirrhotic patients. Previous studies have shown the incidence of VVC to be 55% in noncirrhotic patients, 100% in IPH, and 13-35% in patients with cirrhosis [19,20,32]. A second factor is the difference in the venous pressures in the different hepatic vein branches, with one report indicating that a single venous measurement may underestimate the risk of bleeding from esophageal varices in 13% of cirrhotic patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the pathophysiology of portal hypertension can be assessed on the basis of the absolute value of HVPG [16][17][18]. However, because the results of hepatic venous catheterization are affected by various factors and examination conditions, it may not always be easy to draw reliable conclusions when using continuous variables such as venous pressure data [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…VVC is common in noncirrhotic patients, and the communication routes tend to close as the severity of liver disease increases [8,14]. Thus, the incidence of VVC is 13-35% in cirrhosis patients, 55% in noncirrhotic patients and 100% (37/37) in idiopathic portal hypertension [8][9][10][11]. The HVPG may also differ between branches of the hepatic veins; therefore, it is reported that the single venous measurement may underestimate the bleeding risk from oesophageal varices in 13% of cirrhosis patients [11].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic venography sometimes detects intrahepatic venous-venous communications (VVC), which have an incidence of 13-35% in cirrhosis patients [8][9][10][11]. A recent study has shown that WHVP underestimates the portal pressure in cases with VVC [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation